2019
DOI: 10.3389/fmicb.2019.02681
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence Gene Profiles of Methicillin-Resistant and -Susceptible Staphylococcus aureus From Food Products in Denmark

Abstract: Foods may potentially serve as vehicles for the transmission of antimicrobial-resistant variants of Staphylococcus aureus that are important in a human clinical context. Further, retail food products can be a cause of staphylococcal food poisoning. For these reasons and to account for source attribution and risk assessment, detailed information on the population structure, resistance, and virulence profiles of S. aureus originating from retail food products is necessary. In the current study, whole-genome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 50 publications
6
35
2
Order By: Relevance
“…Although coagulase-positive S. aureus is the most common cause of SFP among staphylococcal species [ 1 ], recent studies have indicated that CoNS can produce SEs and become a potential cause of food poisoning. Staphylococci are normally present in the human and animal microbiota and are frequently found on the skin and in the upper respiratory tract of the host [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although coagulase-positive S. aureus is the most common cause of SFP among staphylococcal species [ 1 ], recent studies have indicated that CoNS can produce SEs and become a potential cause of food poisoning. Staphylococci are normally present in the human and animal microbiota and are frequently found on the skin and in the upper respiratory tract of the host [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These five isolates were all positive for mecA and displayed an OXA-resistant CoPS, Coagulase-positive staphylococci; CoNS, Coagulase-negative staphylococci. 1) SCCmec, staphylococcal cassette chromosome mec.…”
Section: Methicillin Resistance Among Pork-associated Staphylococcimentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the high distributions of etA and etB genes in examined chicken meat samples could be due to the transmission of S. aureus strains from the skin of workers and staffs of slaughterhouses [55]. H Li, P Andersen, M Stegger, R Sieber, H ngmer, N Staubrand, A Dalsgaard and J Leisner [56] reported that the S. aureus strains isolated from poultry meat samples didn't harbor etA and etB virulence factors, while the distribution of the tsst-1 gene was 3.40%. The tsst-1 gene is a super-antigen that can cause a diversity of clinical complications.…”
Section: Discussionmentioning
confidence: 99%